Thermal stratification analysis of triangular integral collector storage solar water heater - Al-Talib, Ammar Abdul Aziz (2009)
The current study outlines the results of testing the effectiveness of using stratification as a collector mechanism for night insulation tool and its effects on the performance of a Triangular Integral Collector Storage (TICS) solar water heater. The main objective of the present work was the desire to develop a new solar water heater design that can be manufactured in Malaysia with the available local materials and labor. It can solve the problem of night cooling that are usually encountered by most of the Integrated Collector Storage (ICS) solar water heaters. The system, in which this solution is incorporated, was referred to as the Triangular Stratified Integrated Collector Storage (TSICS) system. Experimental and numerical investigations were conducted on both the TICS and TSICS systems under thermosyphonic mode with no water draw off. The results obtained showed that the hourly efficiency for the TSICS system is higher than that of the TICS system, and the heat loss at night is less for the TSICS system, indicating more favourable outcomes for the stratified system. FEMLAB software was used to simulate the temperature and velocity distributions in both the TICS and the TSICS systems. The results obtained are in high agreement with the experimental results. In addition, FEMLAB has helped in finding the optimum dimensions for the TSICS system. Architecturally, two possible ways of installing the TSICS system on a pitch roof design were suggested, and for the purpose of this study, they have been called (1) the ‘Floating’ method of installation and (2) the ‘Pocket’ method of installation, whereupon the details and sketches for both were provided The methods of Present Worth and Annual Worth were used for the economic analysis to compare the usefulness of using the TSICS system in comparison to the utilisation of conventional electrical water heaters. Results from both methods have led to the conclusion that using the TSICS solar heater- in spite of its higher initial cost- is more economically superior than using the electrical water heater, hence leading to and substantiating the recommendation of the utilisation of TSICS solar heater system.